2018
DOI: 10.1161/atvbaha.117.310594
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association and Functional Studies Identify SCML4 and THSD7A as Novel Susceptibility Genes for Coronary Artery Disease

Abstract: We identify 3 novel loci associated with CAD and show that 2 genes, and, make functional contributions to atherosclerosis. How rs852787 and its host gene are linked to CAD needs further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 47 publications
1
24
0
1
Order By: Relevance
“…TBX5 is potentially regulated by miR-4455 and it is considered as a key regulator of heart development [56]. Similarly, it was indicated that Scm Polycomb Group Protein Like 4, encoded by SCML4, participates in atherosclerosis mechanism that can lead to ischemic heart disease [57]. In our study, IPA analysis has shown, that miR-1224-5p is involved in the regulation of SCML4 gene.…”
Section: Discussionsupporting
confidence: 60%
“…TBX5 is potentially regulated by miR-4455 and it is considered as a key regulator of heart development [56]. Similarly, it was indicated that Scm Polycomb Group Protein Like 4, encoded by SCML4, participates in atherosclerosis mechanism that can lead to ischemic heart disease [57]. In our study, IPA analysis has shown, that miR-1224-5p is involved in the regulation of SCML4 gene.…”
Section: Discussionsupporting
confidence: 60%
“…Especially, We focus on the co-expression relationship pairs associated with lncRNA ENST00000607042 to explore the potential biological functions in IA. We found that SCML4 is associated with endothelial dysfunction and vascular remodeling [21]. CXCR4, another mRNA co-expressed with lncRNA ENST00000607042, has been reported to be likely to regulate chemotaxis and adhesion through the CXCR4-SDF-1 pathway, which is closely related to cardiac and macrovascular development [45].…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, we observed many mRNAs that may be involved in the pathogenesis of IA. Such as Eukaryotic elongation factor 2 kinase (EEF2K) [ 20 ], Scm polycomb group protein-like 4 (SCML4) [ 21 ], Matrix metalloproteinases 19 (MMP19) [ 22 ], Lymphoid enhancer factor 1 (LEF1) [ 23 ]. The further GO analyses revealed that the co-expression genes of the 5 candidate lncRNAs were related to T cell activation and leukocyte activation, etc.…”
Section: Resultsmentioning
confidence: 99%
“…We further investigated the genetic association with specific lung cancer histological subtypes and identified additional 22 novel loci achieving genome-wide significance (Table 2 and Supplementary Table 2 We observed a novel association in Thrombospondin type 1 domain containing 7A (THSD7A) at rs111754768 on 7p21.3 that demonstrated a strong genetic signal in African-ancestry subjects. THSD7A is known for coronary artery disease susceptibility 49 . We found novel SNPs with strong evidence of associations with SCC at rs139904273 in DLC1 on 8p22 and at rs182805930 in VPS13B on 8q22.2 presenting significant genetic signal in African-ancestry populations, and intergenic variant rs192523071 near CSMD3 on 8q23.3 with significant signal in European-ancestry populations.…”
Section: Resultsmentioning
confidence: 99%